ADDRESSING THE CHALLENGES TO THE INTRODUCTION OF BATTERY ENERGY STORAGE SYSTEMS IN RENEWABLE ENERGY UTILISATION SYSTEMS - Jovanovikj, Eleonora; Manev, Nikola; Dimitrovski, Dame (Journal of Energy Technology, 2025)
The transition to sustainable energy sources is integral to addressing climate change and ensuring long-term environmental resilience. Battery Energy Storage Systems (BESS) play a pivotal role in this transition, by mitigating the intermittency of renewable energy sources such as wind and solar power. However, the widespread deployment of BESS faces significant challenges, including high implementation costs, environmental impacts, grid stability concerns and battery lifecycle management issues. This paper investigates these challenges systematically through a comprehensive literature review methodology, synthesising insights from peerreviewed articles, conference proceedings and technical reports. Common themes and recurring challenges related to BESS implementation are identified and categorised, encompassing technical, economic, regulatory and environmental factors. Furthermore, the effective mitigation strategies and solutions proposed in the literature are analysed and evaluated for their feasibility and applicability. The findings underscore the importance of innovative approaches, such as second-hand battery modules, sustainable production practices, the implementation of advanced operational strategies, and predictive maintenance algorithms, in enhancing the feasibility and efficacy of BESS integration. Additionally, policy incentives and collaborative efforts with utilities and grid operators are highlighted as crucial for promoting grid resilience and reliability. This research contributes to a nuanced understanding of the complexities inherent in advancing sustainable energy infrastructures, and provides valuable insights for policymakers, industry stakeholders, and researchers seeking to address the challenges of BESS deployment in renewable energy utilisation systems.